Pengaruh Pemakaian Lensa Blue Cut Terhadap Kenyamanan Pengguna Gadget Di Optik X Mobile Area Jakarta Barat Tahun 2022 - Husein, Mohammad (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2023)
Based on Ratyanake's research (2018), it shows that blue light hitting the eyes for a long period of time can trigger photoreceptor (light-sensitive) cells to produce toxic molecules that are harmful to the eyes. Based on the Jhonson survey in Indonesia in 2019 in Raharjo (2019), there are 97% of Indonesian people who feel disturbed when they get excessive and blinding light in their eyes in their daily activities. In this study, researchers used secondary and primary data as research data, secondary data was taken from optical sales data and primary data was taken by giving questionnaires to consumers of Optik X mobile area, the sample used in this study amounted to 30 people, for data processing the author uses SPSS 25 software. The results of this study indicate that there is an influence between the blue cut lens and the response that has a positive and significant effect on the comfort of gadget users in the Optik X mobile area, this is based on a hypothesis test (partial t test) with the results of the t value of 6.254 > t table 2,051. This means that H1 is proven correct, so it can be concluded that there is an influence between the use of blue cut lenses on the comfort of gadget users in the Optical Melawai mobile area of West Jakarta.